2022
DOI: 10.1038/s41598-022-23787-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and challenges in management of hemodialysis catheter-related infections

Abstract: Catheter-related infections (CRI) are a major cause of morbidity and mortality in chronic hemodialysis (HD) patients. In this paper, we share our experience with CRI in HD patients. We recorded 49 cases of CRI among 167 patients during a period of 40 months (January 2018–April 2021). The incidence of CRI was 3.7 per 1000 catheter-days. The revealing symptoms were dominated by fever or chills (90%). Inflammatory signs were observed in 74% of cases with respectively concurrent exit-site (51%) and tunnel infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Study by Haiji et al, reported the mean duration of dialysis was 16.5 months in the group with catheterrelated infection and 3.7 months in the group without catheter-related infection (p < 0.04). (23) Study by Shoaib et al, reported majority of CRBSI patients underwent hemodialysis over 6 months (p < 0.05). (14) Shahar et al, reported that the majority of CRBSI patients underwent hemodialysis over 3 month (87%).…”
Section: Discussion Smentioning
confidence: 98%
“…Study by Haiji et al, reported the mean duration of dialysis was 16.5 months in the group with catheterrelated infection and 3.7 months in the group without catheter-related infection (p < 0.04). (23) Study by Shoaib et al, reported majority of CRBSI patients underwent hemodialysis over 6 months (p < 0.05). (14) Shahar et al, reported that the majority of CRBSI patients underwent hemodialysis over 3 month (87%).…”
Section: Discussion Smentioning
confidence: 98%
“…The incidence of C-RBSI caused by Gram-negative bacilli [ 2 , 7 ], while still low, has increased in recent years [ 5 , 6 , 23 ], mainly among oncologic patients and those undergoing hemodialysis [ 1 , 2 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci are the main cause of catheter-related bloodstream infection (C-RBSI). However, the Gram-negative bacillus Escherichia coli , which can form biofilms on the catheter surface, remains an important agent in specific populations, including patients with oncologic–hematological conditions and those undergoing hemodialysis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization duration is prolonged, necessitating increased effort from medical staff and, not least, incurring higher costs [ 27 ]. CVC usage in hemodialysis patients is associated with a 7-fold higher risk of infection compared to those using native FAV and a much consistent risk of the malnutrition–inflammation syndrome compared to those with FAV [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%